Potential of Former Sand Mining Land for Durian Cultivation: Case Study in Ngrogung Village, Ponorogo, East Java - Lis Noer Aini; Ganda Anugrah Marryos; Gunawan Budiyanto; Siva Kumar Balasundram (Agrotechnology Research Journal, 2024)
Ngrogung is one of the sand mining areas in Ponorogo, East Java, Indonesia. Post-mining, this area often remains underutilized. One potential application for this former sand mining land could be the cultivation of durian plants. The research aims to determine land characteristics and evaluate the level of land suitability for Durian cultivation. The research was conducted using survey methods. Determining the research location was carried out purposively based on conditions in the field. The study area is 20 hectares, which is an ex-sand mining area. Determination of representative samples was carried out in a zigzag manner to obtain a representative sample. Soil samples were taken to a depth of 100 cm, representing the root area of the durian plant. Sample analysis was carried out using the method issued by the Land Resources Center, and the results obtained were analyzed using matching methods based on FAO criteria. The results showed that the actual land suitability of the ex-sand mining in Ngrogung Village is S3nr-2 covering an area of 10 hectares with alkaline saturation limiting factor, S3nr-4; eh-2 with C-organic and erosion hazard limiting factor 6 hectares, S3nr-4; rc-2 with C organic and crude material limiting factor 4 hectares. The potential suitability of ex-sand mining land based on FAO criteria can be categorized as S2 (quite suitable), so it requires technological input such as adding organic matter, making terraces, and planting according to contours.